Avoiding Untimely Implantable Cardioverter/Defibrillator Implantation by Intensified Heart Failure Therapy Optimization Supported by the Wearable Cardioverter/Defibrillator—The PROLONG Study. Issue 1 (17th January 2017) - Duncker, David; König, Thorben; Hohmann, Stephan; Bauersachs, Johann; Veltmann, Christian
Abstract : Background: Optimal timing of implantation of an implantable cardioverter/defibrillator (ICD) after newly diagnosed heart failure is unclear given that late reverse remodelling may occur. We aimed to analyze left ventricular ejection fraction (LVEF) after diagnosis of an LVEF ≤35% during optimization of heart failure drug therapy. Methods and Results: One hundred fifty‐six patients with newly diagnosed LVEF ≤35% receiving a wearable cardioverter/defibrillator (WCD) were analyzed. WCD was prescribed for 3 months until first re‐evaluation. Indications for prolongation of WCD wearing period instead of ICD implantation were: (1) LVEF at 3‐month visit 30% to 35%; (2) increase in LVEF of ≥5% compared to the last visit; and (3) nonoptimized heart failure medication. Mean LVEF was 24±7% at diagnosis and 39±11% at last follow‐up (mean, 12±10 months). Whereas 88 patients presented a primary preventive ICD indication (LVEF ≤35%) at 3‐month follow‐up, only 58 showed a persistent primary preventive ICD indication at last follow‐up. This delayed improvement in LVEF was related to nonischemic origin of cardiomyopathy, New York Heart Association functional class at baseline, heart rate, better LVEF after 3 months, and higher dosages of mineralocorticoid receptor antagonist. Twelve appropriate WCD shocks for ventricular tachycardia/ventricular fibrillation occurred in 11 patients. Two patients suffered from ventricular tachycardia/ventricular fibrillation beyond 3 months after diagnosis. Conclusions: A relevant proportion of patients with newly diagnosed heart failure shows recovery of LVEF >35% beyond 3 months after initiation of heart failure therapy. To avoid untimely ICD implantation, prolongation of WCD period should be considered in these patients to prevent sudden cardiac death while allowing left ventricular reverse remodeling during intensified drug therapy.